The ghosts of the past, present and future: the case of the Army Headquarters in Belgrade, Serbia - Milošević, Srđan (Journal of Architecture and Urbanism, 2015)
When the construction of Dobrović’s Army Headquarters in Belgrade, Serbia was finally finished in 1965, at a location continuously designated for the Army, it was thought that it would serve its purpose in a secured future, the socialist one. And it was thought that it would house the leadership of the Army, which was seen as the rightful heir of the most glorious examples of military tradition from the Second World War. With his building Dobrović filled the void left by the WWII, but he also left a true mystery – how to interpret it. Long after the date of inception, in 1960, he offered two clues, the philosophical one – through the Bergson’s dynamic schemes and the void as the central dynamizing element of the composition and the symbolically appropriate one – through the story of the Sutjeska canyon. In this way he allowed everyone to find a reading suitable for them. But when the system changed, followed by a decrease in size of both the State and the Army, the question of the dual reading, which functioned so perfectly, suddenly became the cause of conflicts, conflicts of a more profound nature than ever before. Even in these changed circumstances the building performed its function, until the 1999 NATO aggression, when it was, although empty, bombed several times. The history repeated itself and this location once again experienced bombardment which left disturbing ruins, voids and shattered identities, in need of renegotiation. How to interpret a building from a socialist period in a society which is both post-socialist and post-conflict? How to find peace with the ghosts of the past, present and future, which permeate both the location and the building? How to approach different narratives surrounding the physical structure destroyed by war and considered as heritage even before those events, although officially listed only after the ruination and cessation of use. Those are the main subjects of this article.